Effectiveness of Tourism Awareness Groups in Developing Tourism Potential in Desa Wisata Jangga Dolok Kecamatan Lumban Julu Kabupaten Toba - Manurung, Hanna; Panjaitan, Ade Putera Arif; Simbolon, Rusmauli; Nadeak, Tio R J; Firmando, Harisan Boni (Contemporary Journal of Applied Sciences, 2023)
The aim of this research is to determine the effectiveness of the performance of Pokdarwis in Jangga Dolok Village, Lumban Julu District, Toba Regency. As well as the efforts that have been made by Pokdarwis Jangga Dolok in developing the tourism potential in the village. This research uses descriptive qualitative methods and the data collection techniques used in this research are: Observation, interviews and documentation. In this research there are two types of informants, namely: key informants and ordinary informants. This research consists of two types of primary data and secondary data. This research found that the performance of Pokdarwis Jangga Dolok was effective with the efforts made by Pokdarwis through activities and programs that had been implemented in Jangga Dolok Village in 2022